Zwitterionic coating on thin-film composite membranes to delay gypsum scaling in reverse osmosis - Jaramillo, Humberto; Boo, Chanhee; Hashmi, Sara M.; Elimelech, Menachem (ELSEVIER, 2021)
Precipitation of calcium sulfate dihydrate (i.e., gypsum) on the membrane active layer negatively impacts the efficiency of reverse osmosis (RO) systems by increasing overall operation and maintenance costs. The interfacial free energy between RO membranes and scalants is expected to play a paramount role in crystal nucleation and adsorption. In this work, we modified the surface of a thin-film composite RO membrane with a zwitterionic polymer brush via atom transfer radical polymerization (ATRP) to impart superhydrophilicity for enhanced resistance to gypsum scaling. The zwitterionic polymer coating was optimized and a highly hydrophilic membrane surface displaying a water contact angle of <20. was achieved. Characteristics of both the control and the zwitterion-modified RO membranes such as surface roughness, chemical composition, and surface energy components, were investigated to elucidate the factors controlling gypsum scaling behavior. Results from benchscale RO scaling experiments indicate that membranes modified with the zwitterionic brush effectively delay gypsum surface nucleation and crystal adsorption relative to the control membrane. At the end of the RO scaling experiments with only-heterogeneous gypsum nucleation, the zwitterion-modified membrane exhibited a flux decline of 23.7% (relative to the initial water flux), much smaller than a 49.5% flux decline of the control RO membrane. We further verified that a precipitous flux decline by deposition of gypsum crystals in the combined homogeneous and heterogeneous nucleation pathway was about 1.6 times delayed for the zwitterion-modified membrane compared to the control RO membrane. Our results highlight that developing a more hydrophilic membrane surface is crucial to resisting gypsum scaling in RO systems.
Keywords: CALCIUM-SULFATE DIHYDRATE; MODELING CONCENTRATION POLARIZATION; OF-THE-ART; SURFACE MODIFICATION; PHYSIOCHEMICAL PROPERTIES; NANOFILTRATION MEMBRANES; FOULING RESISTANCE; BLOCK-COPOLYMER; CRYSTAL-GROWTH; FLUX DECLINE